Understanding Continuance Usage of Mobile Learning Applications: The Moderating Role of Habit - Wang, Yi-Ting; Lin, Kuan-Yu (Frontiers in Psychology, 2021)
This study explored the factors that affect users’ intention to continue using mobile learning (m-learning) applications (apps). The influence of habit on user behavior toward information systems has been extensively discussed in the literature, but its role in users’ continuance usage of apps, especially m-learning apps, has rarely been reported. To obtain a comprehensive understanding of behaviors regarding the use of m-learning apps, this study constructed a theoretical research framework based on expectation confirmation theory and flow theory by considering habit as a moderating variable. Online questionnaires were administered to users of m-learning apps in Taiwan and data were analyzed through structural equation modeling approach. The results indicate that users’ intention to continue using m-learning apps is influenced by satisfaction, perceived usefulness, and flow experience. Expectation confirmation affects user satisfaction and perceived usefulness. Differences exist in the intention to continue usage between users with strong and weak habits. In addition, perceived usefulness, expectation confirmation, and flow experience have direct and positive effects on satisfaction. The implications of these findings are discussed.